2019
DOI: 10.1016/j.ygeno.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression, function, and evolution of miR-27 isoforms and their responses in metabolic processes

Abstract: This study aimed to discuss the potential roles of isomiRs of miR-27 family in metabolisms associated with disease via analyses of their evolution, expression, and function. miR-27b-3p was relatively highly expressed in liver cancer samples compared to miR-27a-3p and miR-27-5p loci. The diversity of isomiRs in miR-27-3p locus is similar to that of miRNAs among homologous genes. IsomiRs exhibited variable expression across different cancer tissue types, and some of them were abnormally expressed in ob/ob mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Of note, these previous reports dealt with the mature miR-205-5p and miR-574-3p whereas our diagnostic panel included isomiR. The two types were previously thought to have a similar function because of their similar sequence, but more recent studies have identified that they have different functions [19,43,44]. In fact, the target messenger RNA of isomiR has concordance and discordance with mature miR, in accordance with the difference between them in sequence [45].…”
Section: Plos Onementioning
confidence: 72%
“…Of note, these previous reports dealt with the mature miR-205-5p and miR-574-3p whereas our diagnostic panel included isomiR. The two types were previously thought to have a similar function because of their similar sequence, but more recent studies have identified that they have different functions [19,43,44]. In fact, the target messenger RNA of isomiR has concordance and discordance with mature miR, in accordance with the difference between them in sequence [45].…”
Section: Plos Onementioning
confidence: 72%
“…In liver cancer, miR-27a-3p has a high expression level of isomiR in normal cells, while isomiR expression is decreased significantly in tumor cells. However, this differentiation is not observed at the homologous miR-27b-3p site, indicating that isomiR-27a may have a more complicated background in tumor cells (20). As a 22-nt long mimic, it is easy for miR-27a to cooperate with other miRs.…”
Section: Biogenesis Of Mir-27a In Solid Tumorsmentioning
confidence: 98%
“…The miR-27 family (containing miR-27a and miR-27b), a highly conserved miRNA family across different species, are encoded on different chromosomes and share analogous seed sequences with a nucleotide difference at the 3 0 end. 13 Recent research has suggested that miR-27a can increase the expression of β-MHC gene in ventricular myocytes. 14…”
mentioning
confidence: 99%